THE ROLE OF RELIGIOUS LEADERS IN STRENGTHENING AQIDAH IN NYADRAN TRADITION IN WONOGIRI DISTRICT, CENTRAL JAVA PROVINCE - Supriyanto Supriyanto; Devi Sulastri; Amrin Amrin (Profetika: Jurnal Studi Islam, 2022)
This study aims to determine the role of Islamic religious leaders in straightening aqidah in the Nyadran tradition in Wonogiri Regency, Central Java Province. This type of research uses a qualitative type with field studies in Plosorejo Village, Kismantoro District. While the research approach used is descriptive analysis. The data analysis used is using inductive analysis with an ethnographic approach. The results showed that the role of religious leaders in rectifying the aqidah related to the Nyadran tradition in Plosorejo Village, Kismantoro District, Wonogiri Regency was quite good starting as a spiritual leader, builder and claimant of the people and as a builder of social ethics through inclusive and varied methods. The role of religious leaders has sacredness in people's lives in Plosorejo Village,